The Transfer of Meaning via Contextually Controlled Equivalence Relations - Perez, William F.; dos Santos Zuppani, Tatiani; Dorigon, Andrea Hey; de Vasconcellos, Eduardo Luciano; da Silva, Marco Aurélio; Lima, Najra Danny Pereira; de Almeida, Roberta Bianca Marcelino; Montan, Rodrigo Noia Mattos; de Almeida, João Henrique [UNESP]; de Rose, Julio C. (Springer Nature, 2023)
The present study aimed to evaluate the transfer of meaning in equivalence classes under contextual control. Adult participants were exposed to relational training and testing to establish equivalence relations between facial expressions of fear (A1) and happiness (A2) and nonsense stimuli (C1 and C2). The equivalence relations were under contextual control. Thus, in Context 1, C1 was equivalent to A1 (fear), and C2 was equivalent to A2 (happy); in Context 2, the relations between A and C stimuli were reversed (i.e., A1(fear) was equivalent to C2 and A2(happy) was equivalent to C1). The meaning of C1 and C2 stimuli under Context 1 and 2 were assessed using a semantic differential. As predicted, the meaning of C stimuli depended on the context in which they were presented and cohered with the equivalence relations established in those contexts. We conclude that the semantic differential is an instrument that captures context-dependent meaning (functions).
Keywords: Contextual control; Equivalence relations; Fearful faces; Happy faces; Semantic differential; Transfer of function